Colonial Displacement and Subjectivity in V. S. Naipaul’s A House for Mr. Biswas - Giri, B. P. (Literary Studies, 2015)
Judging by the critical acclaim it has received over the years, V. S. Naipaul’s A House for Mr. Biswas (1961) has become essential reading in the canons of postwar British and Anglophone postcolonial fiction. Based closely on the life of Naipaul’s father, it can be read as a novel of Indian indenture diaspora par excellence (Mishra, 1-23), as it chronicles the biography of Mohun Biswas and his life-long struggle to free himself from the shadow of the Tulsis, a powerful landowning family into which he marries, as reflected in his attempts to build a house for himself and secure a stable livelihood and source of income. The early part of the novel sketches a picture of the Indian indentured diasporic life in Trinidad, characterized by utter desolation, poverty, and marginality. In a chapter titled “Pastoral” that is anything but bucolic in its tenor, the reader is provided with an occasional glimpse into Biswas’s maternal grandfather’s uprooting from India: